STUDI FENOMENOLOGI : DUKUNGAN TERHADAP KEPATUHAN MINUM OBAT PADA PENDERITA TUBERCULOSIS DENGAN MULTIDRUG-RESISTANT - Murwanti Murwanti (Jurnal Delima Harapan, 2021)
Background: Tuberculosis is an infectious disease if the patient does not complete therapeutic treatment can cause multidrug-resistant tuberculosis (MDR-TB). The role of the environment is needed to support treatment.The study aims to explore more deeply the family's support for medication adherence in patients with multidrug-resistant tuberculosis (TBC-MDR). Method: This type of research is qualitative using a descriptive phenomenological approach, in-depth interviews of 5 participants based on purposive sampling technique. Results: The results of the study found the role of the family towards TB-MDR patients manifested in emotional, physical, instrumental, and spiritual support. emotional support consists of positive and negative emotional. Community involvement after counseling was supportive but there were some who could not accept even families of MDR-TB sufferers were also shunned. The role of health services is to convey information, prepare medicines, supervise, motivate treatment, remind check schedules, refer to more complete facilities when needed, visit homes and ensure patients take medication if unable to come to the public health service. Conclusion: This study found 3 main themes, namely the role of comprehensive family, community involvement and the role of health services in mentoring TB-MDR patients.